আমার রাজনীতির ৬০ বছর : জোয়ার-ভাটার কথন - আহমদ, কাজী জাফর (ঢাকা : তরফদার প্রকাশনী, 2017)
Autobiographical reminiscences of Kājī Jāphara Āhamada, politician from Bangladesh; chiefly about his political career.
গ্রন্থপঞ্জিগত নির্দেশিকা (পৃষ্ঠা ৪৫৫-৪৫৬) ও নির্ঘণ্ট অন্তর্ভুক্ত।
Donated By Akbar Ali Khan
In Bengali; includes passages in English.
Keywords: Āhamada, Kājī Jāphara -- Political activity; Politicians -- Bangladesh -- Biography; Bangladesh -- Politics and government -- 1971.; Bangladesh -- Biography